Celiac Disease in an Adoptive Child with Recurrent Giardia Infection - Tchidjou, Hyppolite K.; De Matteis, Arianna; Di Iorio, Laura; Finocchi, Andrea (International Journal of Health Sciences, 2015)
Celiac disease (CD) is an inflammatory disease of the small intestine. A complete management and differential diagnosis of such disease includes food intolerances, intestinal infections, and irritable bowel syndrome.We describe an 8-years-old adoptive girl from Congo with negative medical history. Patient followed for recurrent abdominal pain and diarrhea associated to Giardia infection, unresponsive to antiparasitic therapy. Persistence of symptoms despite antiparasitic therapy, prompted us to perform: 1- Blood screening of Celiac disease, which was negative; 2- Genetic evaluation of celiac disease, which revealed the presence of HLA-DQ2 heterodimer; and 3- Esophagogastroduodenoscopy, which showed duodenal villous atrophy and crypt hyperplasia, associated with Helicobacter Pylori infection. The child was treated in accordance with international recommendations using a Gluten-free diet and specific antibiotics, which lead to the resolution of the symptoms. Our patient’s clinical history seems peculiar, considering that, recurrent Giardiasis may mimic the symptoms of Celiac disease and may simulate clinical and histological picture of active Celiac disease. Early diagnosis may help prevent the complications of untreated celiac disease. Key Words: Recurrent Giardiasis, Celiac Disease, Intestinal Parasitosis